Penanaman Sikap Gotong Royong Dalam Kegiatan Ekstrakurikuler Pramuka Di SDN 3 Kronggen Grobogan - Djamari, Djamari; , Prof. Dr. Sutama, M.Pd; , Dr. Suyatmini, M.Si (2016)
The purpose of this research (1) Implantation the attitude of mutual cooperation with habituation in ekstrakurikuler scout activities (2) evaluation of Implantation an attitude of mutual cooperation with exemplary ekstrakurikuler scout activities (3) Implantation constraints attitude of mutual cooperation in the activities ekstrakurikuler scout. Data collection techniques of observation, interviews and documentation. Data analysis techniques: data collection, data reduction, data presentation, and conclusion. Test the validity of data triangulation. The results of this study were (1) Implantation attitude of mutual assistance in the implementation of activities that ekstrakurikuler scout scout extracurricular activities of students together and mingle with other woods classes, cooperation in carrying out the task group, a gotong royong to clean the school yard. The process of preparation of the implementation of the scouts hold mugus and form a management committee. (2) The parties involved in the evaluation is the principal, teachers as a scout leader and school committee held after the completion of activities, one month and six months. Things that are evaluated include the presence of students, the suitability of the material. achievement of the program charge (3) Constraints faced by the implementation of extracurricular activities such as student scouts came in late, students lack enthusiasm and focus not receive the material to weather factors. How to overcome obstacles is to give more tasks that can foster a sense of mutual cooperation, discipline children who are often late, do a variety of teaching, giving concrete examples of Trustees scout.